Opening up the innovation system framework towards new actors and institutions - Warnke, Philine; Koschatzky, Knut; Dönitz, Ewa; Zenker, Andreas; Stahlecker, Thomas; Som, Oliver; Cuhls, Kerstin; Güth, Sandra (Fraunhofer ISI discussion papers innovation systems and policy analysis, 2016)
The paper revisits the established framework of the national and regional innovation system (NIS/RIS) in the light of recent insights from innovation research in order to increase its capacity for generating meaningful insights for policy makers and other actors wishing to influence innovation capacity of nations, regions or sectors. We review six research strands that challenge the classical NIS/RIS framework by pointing to a wider range of actors, institutions and innovation modes relevant for the innovation landscape: User innovation, social innovation, collaborative innovation, new innovation intermediaries, venture philanthropy, social and relational capital and non-R&D intensive industries. We find that each of these phenomena points to relevant contributions to national or regional innovation capacities that are not well captured by the established NIS/RIS framework. While some aspects could easily be integrated by adding some "arrows and boxes" in the graphics usually used for representing the framework, we find that several phenomena point to the need for a more fundamental revision of the innovation system framework. In particular it emerges that a distinctive assignment of actors to functions in the innovation process is no longer possible. Given, for example, the research insights on user innovation, social innovation and collaborative innovation, societal actors can no longer be assigned to the role of "demand articulation". Rather they actively contribute or sometimes even take over the generation of knowledge and innovation ideas as well as other functions such as financing, e.g. through crowdfunding activities. The broadened view on innovation also requires a wider understanding of the infrastructures and frameworks forming the enabling basis for innovation activities. Social and relational capital for instance that is deeply embedded in the cultural context of a region becomes a key enabler for trustful interactions of the diverse innovation actors such as low R&D intense firms that make huge contributions to innovation and employment but generate their knowledge through interaction with customers. The growing recognition of the economic and social relevance of collaborative and social innovation implies that collaboration platforms become as relevant infrastructures as classical technology transfer schemes. Finally the broadened view on innovation points to a wide range of intermediaries that form the backbone of an innovation system without necessarily seeing innovation as their primary purpose. As a consequence of these insights we suggest a revised innovation system framework. This system captures three types of contributions: Innovation supply and demand, innovation influx and innovation framework. Actors that may provide relevant contributions in one of these domains are grouped in open clouds, emphasizing the fluidity between functions and actors. We hope that this framework will allow for a more meaningful analysis of the innovation capacity of specific NIS/RIS systems.
Keywords: Arbeitspapier; Graue Literatur